Chapter 87 Scalar implicature as a grammatical phenomenon - Chierchia, Gennaro (De Gruyter, 2012)
This article develops various arguments for the view that scalar implicatures should be de-rived within grammar and not by a theory of language use (pragmatics). We focus primarily on arguments that scalar implicatures can be computed in embedded positions, a conclusion incompatible with existing pragmatic accounts. We also briefly review additional observations that come from a variety of empirical domains, all incompatible with pragmatic accounts, yet predicted by the grammatical alternative.